Risk Prevention and Quality Control in Camel Milk Collection: Insights from Field Research - Hui Yang; Demtu Er; Yuning Liu; Hongxia Ling; Rili Ge (Foods)
The camel milk market’s rapid expansion necessitates strategies that ensure raw milk quality and safety, particularly in small-scale production. This study examines smallholder farmers in Haixi, Qinghai Province, China, where traditional practices intersect with modern standards. Analyzing 80 raw camel milk samples, the study assessed risks like adulteration, microbial contamination, and nutritional variability. DNA testing and microbial assays revealed that 66.67% of hand-milked samples were adulterated with cow milk, a significantly higher rate than mechanically processed samples (p < 0.05). Manual milking also showed higher microbial counts (up to 2.05 × 104 CFU/mL) and somatic cell levels, indicating hygiene issues. Nutritional analysis found that grazing systems yielded milk with more vitamin A, B2, and potassium, while semi-intensive systems had higher ash content. A quality evaluation framework was developed, combining pastoralist knowledge with rapid diagnostic tools, focusing on mechanization, cold-chain efficiency, and community training. This framework provides strategies to reduce adulteration, ensure nutritional consistency, and align small-scale production with international standards. The study proposes culturally adaptive quality control methods to protect consumer health, support rural livelihoods, and standardize the camel milk market.